Counseling and Training to Improve The Level of Dental and Oral Health in Junior High School Taman Siswa Belawan Medan - Manja, Cek Dara; Nasution, Rini Octavia; Kartika, Dewi; Sitanggang, Maria NH (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2025)
SMP Taman Siswa Belawan Medan, North Sumatra, faces significant dental and oral health issues, particularly among students who suffer from cavities and periodontal problems. Additionally, anxiety about dental visits and radiographic examinations further complicates efforts to improve oral health. This community service program aims to enhance knowledge and skills related to oral health through counseling, proper tooth-brushing training, and intra-oral radiographic examinations. The program was conducted in two phases: the first phase involved counseling and training, while the second phase focused on evaluation. The evaluation results indicated a significant increase in knowledge. In the pre-test, 28% of students had good knowledge, 56.67% had sufficient knowledge, and 15.33% had poor knowledge; following the intervention, 60% had good knowledge, 30.67% had sufficient knowledge, and 9.33% had poor knowledge. For teachers, the pre-test showed 52.94% with good knowledge, 47.06% with sufficient knowledge, and 0% with poor knowledge, which increased to 100% with good knowledge in the post-test. This program was effective in raising awareness and knowledge about oral hygiene, cavity prevention, and the importance of dental check-ups, which ultimately contributed to reducing the prevalence of dental problems among students and teachers, thereby improving overall oral health.Keywords: Counseling, Dental and Oral Health, Training   Abstrak: SMP Taman Siswa Belawan Medan, Sumatera Utara, menghadapi masalah kesehatan gigi dan mulut, terutama di kalangan siswa, yang banyak menderita gigi berlubang dan gangguan jaringan periodontal. Selain itu, kecemasan terhadap kunjungan ke dokter gigi dan pemeriksaan radiografi juga menjadi hambatan dalam upaya perbaikan kesehatan gigi. Program pengabdian masyarakat ini bertujuan untuk meningkatkan pengetahuan dan keterampilan kesehatan gigi melalui penyuluhan, pelatihan cara menyikat gigi yang benar, serta pemeriksaan radiografi intra-oral. Program ini dilaksanakan dalam dua tahap, yaitu tahap pertama berupa penyuluhan dan pelatihan, sedangkan tahap kedua adalah evaluasi. Hasil evaluasi menunjukkan peningkatan pengetahuan yang signifikan. Pada pretest, 28% siswa memiliki pengetahuan yang baik, 56.67% cukup, dan 15.33% kurang; sedangkan pada post-test, 60% memiliki pengetahuan baik, 30.67% cukup, dan 9.33% kurang. Pada guru, hasil pretest menunjukkan 52.94% memiliki pengetahuan baik, 47.06% cukup, dan 0% kurang, yang meningkat menjadi 100% pada post-test. Program ini terbukti efektif dalam meningkatkan pengetahuan tentang kebersihan gigi dan mulut, pencegahan gigi berlubang, serta pentingnya pemeriksaan gigi, yang pada akhirnya dapat menurunkan prevalensi masalah gigi di kalangan siswa dan guru serta meningkatkan kesehatan gigi dan mulut secara keseluruhan.  Kata kunci: Kesehatan Gigi dan Mulut, Penyuluhan, Pelatihan